DESIGNING A SUSTAINABLE SOCIAL PROTECTION SYSTEM IN UKRAINE: A COMPREHENSIVE EVALUATION - Анжела Ігнатюк; Мартіна Раштіцова; Наталія Приказюк; Антоніна Шолойко; Наталія Ткаленко; Наталія Версаль (Фінансово-кредитна діяльність: проблеми теорії та практики)
Social values hold heightened importance, particularly during wartime. Ukraine's social protection system is designed to help vulnerable groups of people, yet it faces financial constraints, with many resources being redirected towards military needs. Consequently, evaluating its effectiveness is crucial, and it is essential to develop recommendations to enhance its resilience and adaptability. The goal of this research is to evaluate the social protection system of Ukraine and to make recommendations to fill the gaps in its functioning. The evaluation of Ukraine's social protection system utilized the Core Diagnostic Instrument (CODI tool) from the Inter-Agency Social Protection Assessments to the extent possible, given the constraints posed by limited information availability. This tool consists of four modules: policy, program design, program implementation, and system assessment guidelines. Thirteen experts from Ukraine provided an assessment of eight criteria. This comprehensive evaluation of Ukraine's social protection system allows for the identification of its strengths and weaknesses. The social protection system of Ukraine was evaluated, receiving an average score of 2.5 out of 4. Strengths include a well-developed legislative base for social protection and the use of a program-targeted method for implementing budget programs with social dimensions. However, weaknesses were also identified, such as low levels of social standards, insufficient funding, numerous social protection authorities with potential duplications and overlaps in their activities, and a weak information dissemination system regarding the realization of social protection goals. Several measures are needed to address the shortcomings in Ukraine's social protection system: raising the level of social standards to better reflect current economic conditions and consumer price trends; reviewing the sources of financing for social protection programmes to ensure a more effective allocation of resources; and modernising the social protection reporting system to improve the decision-making process. The implementation of these recommendations will contribute to the development of a more adaptable and resilient social protection system in Ukraine.